Credit Risk Management and Profitability of Selected Deposit Money Banks in Nigeria: Panel Data Approach: Array - Olaoye, Festus Oladipupo; Fajuyagbe, Samson Bamikole (The Journal of Accounting and Management, 2020)
The study investigated effects of credit risk management on the profitability of selected deposit money banks in Nigeria. Specifically, the study analyzed the impact of non-performance loans on return on assets as well as the impact of provision for doubtful debts on return on assets of the selected deposit money banks in Nigeria. The study focused on 10 deposit money banks randomly selected from 21deposit money banks listed on the Nigeria stock exchange. Data were sourced from the published annual financial reports of the selected deposit money banks over a period of 10 years, between 2008 to 2017. Single panel based model was used in the study to capture the interrelationship between credit risk management and profitability of deposit money banks. Profitability measured in terms of return on assets was specified as a function of credit risk management variables including non-performing loans, and provision for doubtful debts. Data collated were analyzed using both descriptive and inferential methods of analysis. Descriptive analysis conducted in the study included mean analysis, measure of dispersion, minimum and maximum analysis, followed by correlation analysis, pooled OLS estimation, fixed effect estimation, random effect estimation, and post estimation test such as restricted F-test, Hausman test, Pesaran cross sectional independence test, Wald test of heteroscedasticity and Wooldridge test of serial autocorrelation. Results show that non-performing loans exert insignificant positive impact on return on assets, with coefficient estimate of 0.0001223(p=0.909 > 0.05), impact of provision for doubtful debts on return on assets is positive and significant, with coefficient estimate of -0.0183529 (p=0.445 > 0.05). Reported R-square for the pooled OLS estimation stood at 0.5276, which implies that credit risk variables including non-performing loans and provision for doubtful debts can only explain about 53% of the systematic variation in return on assets, when heterogeneity effect across sampled deposit money banks is incorporated into the model. Based on the findings, the study concluded that, risk management measured in terms of non-performing loans exert insignificant negative impact on profitability of deposit money banks, while, provision for doubtful debts had positive and significant effect on the profitability of deposit money banks in Nigeria. The study recommended that, automated credit tracking mechanism should be put in place by management of deposit money banks so as to reduce the possibility of default and outstanding loans beyond the substandard loan level of between 90 to 180 days. By so doing the rate of doubtful loans will drastically reduce, such that provision for doubtful debts will be kept at a minimal level.